2012
DOI: 10.1093/rheumatology/kes054
|View full text |Cite
|
Sign up to set email alerts
|

Radiological cervical spine involvement in young adults with polyarticular juvenile idiopathic arthritis

Abstract: Structural cervical spine involvement is common in pJIA persisting into adulthood, frequently asymptomatic and associated with a more severe disease. We suggest that radiographic assessment of the cervical spine should be done systematically at onset of the disease and regularly during its course regardless of clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 26 publications
2
28
1
2
Order By: Relevance
“…Inflammation of the spine and coxofemoral joints is an indicator of more serious forms of the disease. 19,36,37 In our study, spreading to the cervical spine and coxofemoral joints arthritis were only found in children with detectable IL-17A values in the active phase of JIA. Therefore, children with detectable IL-17A levels should be closely monitored, and such results imply that, on the basis of IL-17A values in the initial phase of JIA, it may be possible to select patients at a higher risk from a worse functional outcome.…”
Section: Discussioncontrasting
confidence: 45%
“…Inflammation of the spine and coxofemoral joints is an indicator of more serious forms of the disease. 19,36,37 In our study, spreading to the cervical spine and coxofemoral joints arthritis were only found in children with detectable IL-17A values in the active phase of JIA. Therefore, children with detectable IL-17A levels should be closely monitored, and such results imply that, on the basis of IL-17A values in the initial phase of JIA, it may be possible to select patients at a higher risk from a worse functional outcome.…”
Section: Discussioncontrasting
confidence: 45%
“…The indolent process of leucocyte infiltration into the synovium and proliferation of the synovial tissue lead to a subacute type of inflammation, which may justify that pain is not the most conspicuous feature of clinical presentation of JIA, that may pain be missed, particularly in oJIA [13]. This may justify the frequent absence of neck pain in JIA, regardless of CSI, and its worse prognosis [3].…”
Section: Case Seriesmentioning
confidence: 99%
“…Pain is frequently absent, even in cervical arthritis [3,14]. In the 6 cases described in the literature, at least 3 patients had no pain, at least transitorily, during a few weeks.…”
Section: Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Любой сустав может являться мишенью ювениль-ного артрита, однако наиболее часто поражаются крупные и средние суставы, а именно коленные, голеностопные, лучезапястные, локтевые, тазобед-ренные, реже -мелкие суставы кистей и стоп. При тяжелых вариантах течения заболевания во-влекаются «синовиальные суставы» шейного отдела позвоночника и височно-нижнечелюстной сустав с развитием деформирующего артроза [12,15,19].…”
unclassified